Recombinant nanobody against MUC1 tandem repeats inhibits growth, invasion, metastasis, and vascularization of spontaneous mouse mammary tumors. Issue 2 (19th November 2021) - Merikhian, Parnaz; Darvishi, Behrad; Jalili, Neda; Esmailinejad, Mohammad Reza; Khatibi, Azadeh Sharif; Kalbolandi, Shima Moradi; Salehi, Malihe; Mosayebzadeh, Marjan; Barough, Mahdieh Shokrollahi; Majidzadeh‐A, Keivan; Yadegari, Fatemeh; Rahbarizadeh, Fatemeh; et al.
Abstract : Alteration in glycosylation pattern of MUC1 mucin tandem repeats during carcinomas has been shown to negatively affect adhesive properties of malignant cells and enhance tumor invasiveness and metastasis. In addition, MUC1 overexpression is closely interrelated with angiogenesis, making it a great target for immunotherapy. Alongside, easier interaction of nanobodies (single‐domain antibodies) with their antigens, compared to conventional antibodies, is usually associated with superior desirable results. Herein, we evaluated the preclinical efficacy of a recombinant nanobody against MUC1 tandem repeats in suppressing tumor growth, angiogenesis, invasion, and metastasis. Expressed nanobody demonstrated specificity only toward MUC1‐overexpressing cancer cells and could internalize in cancer cell lines. The IC50 values (the concentration at which the nanobody exerted half of its maximal inhibitory effect) of the anti‐MUC1 nanobody against MUC1‐positive human cancer cell lines ranged from 1.2 to 14.3 nm . Similar concentrations could also effectively induce apoptosis in MUC1‐positive cancer cells but not in normal cells or MUC1‐negative human cancer cells. Immunohistochemical staining of spontaneously developed mouse breast tumors prior to in vivo studies confirmed cross‐reactivity of nanobody with mouse MUC1 despite large structural dissimilarities between mouse and human MUC1 tandem repeats. In vivo, a dose of 3 µg nanobody per gram of body weight in tumor‐bearing mice could attenuate tumor progression and suppress excessive circulating levels of IL‐1a, IL‐2, IL‐10, IL‐12, and IL‐17A pro‐inflammatory cytokines. Also, a significant decline in expression of Ki‐67, MMP9, and VEGFR2 biomarkers, as well as vasculogenesis, was evident in immunohistochemically stained tumor sections of anti‐MUC1 nanobody‐treated mice. In conclusion, the anti‐MUC1 tandem repeat nanobody of the present study could effectively overcome tumor growth, invasion, and metastasis. Abstract : The authors studied the preclinical efficacy of a recombinant nanobody against MUC1 tandem repeats in suppressing tumor growth, angiogenesis, invasion, and metastasis. Expressed nanobody demonstrated specificity only toward MUC1‐overexpressing cancer cells and could internalize in cancer cell lines. Constructed nanobody could effectively overcome tumor growth, invasion, and metastasis.